Lyddie - Paterson, Katherine (New York : Puffin Books, 1992)
Impoverished Vermont farm girl Lyddie Worthen is determined to gain her independence by becoming a factory worker in Lowell, Massachusetts, in the 1840s.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
6.5.
6.5
5-8
Keywords: Factories -- Fiction; Historical fiction; Self-reliance -- Fiction; Textile workers -- Fiction; Weaving -- Fiction; Work -- Fiction; Factories -- Fiction; Historical fiction; Self-reliance -- Fiction; Textile workers -- Fiction; Weaving -- Fiction; Work -- Fiction; Lowell (Mass.) -- Fiction; Lowell (Mass.) -- Fiction